Amine-bridged binuclear palladium(II) complexes with inosine. Equilibrium studies and DFT calculations - Weber, Immo; Puchta, Ralph; Shoukry, Mohamed M.; et al. (Journal of Coordination Chemistry, 2013)
Complex-formation equilibria involving trans-diamine palladium(II) (Pd II), 4,4′-bipyridine (bpy), and inosine were investigated at 25 °C and 0.1 M (NaNO3) ionic strength. The stability constants of all possible mono-nuclear and binuclear complexes were determined. The concentration distribution diagram for the binuclear complexes of PdII-bpy-inosine reveals the complexes that predominate in the physiological pH range and the quite feasible interaction of the binuclear complex PdII-bpy-Pd II with inosine as a DNA constituent. On the basis of DFT calculations (B3LYP/LANL2DZp), the structures of the investigated equilibrium species show typical bond lengths for Pd-O and Pd-N bonds. The C-C bond in [Pd(4,4′-bpy)(NH3)2(OH2)]2+ is clearly shortened to 1.47 Å, leading to reduced aromaticity in bpy. Comparison with model compounds suggests that the uncoordinated aromatic ring can be understood as an electron donating group. © 2013 Taylor & Francis.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Aromaticity; DFT; Kinetic; Palladium 4; 4'-bipyridine